Prospective study of serum uric acid levels and stroke in a Chinese hypertensive cohort. (18th August 2017) - Shi, Xiuli; Yang, Juan; Wang, Liwei; Zhao, Min; Zhang, Chunyan; He, Mingli; Qin, Xianhui; Tang, Genfu; Li, Jianping; Zhang, Yan; Huo, Yong; Cai, Yefeng; et al.
ABSTRACT: Our aim was to investigate the association between serum uric acid (SUA) levels and the risk of first stroke in a Chinese population of hypertensive patients. This prospective study enrolled 20, 577 hypertensive participants who without a history of stroke, and was conducted from May 2008 to August 2013 in Anqing and Lianyungang (China). A total of 632 (3.1%) first stroke events (510 ischemic events, 120 hemorrhagic events and 2 unspecified stroke events) were identified during a mean 4.5-year follow-up period. The risk of first stroke was not significantly associated with the increased SUA levels; this conclusion was also found after adjustment for gender and age. However, a statistically significant decreased risk of hemorrhagic stroke for the second SUA quartile (Q2) compared to the first quartile (Q1) (HR 0.56, 95%CI: 0.32–0.97, P = 0.037) was found. In addition, when grouped by tertiles of diastolic blood pressure (DBP), the results showed that high SUA lowered the risk of total stroke in participants in the third SUA quartile (Q3) (HR 0.69, 95%CI: 0.49–0.96, P = 0.028) and fourth SUA quartile (Q4) (HR 0.70, 95%CI: 0.50–0.99, P = 0.043) as compared with that in the first quartile (Q1). To sum up, no significant evidence in present study indicates that increased SUA levels are predictive of first stroke in a Chinese population of hypertensive patients.